Così fan tutte opera buffa in two acts, K. 588 (1790) - Mozart, Wolfgang Amadeus 1756-1791 (Naxos Rights (Europe) Ltd., 2022)
The focus of Lorenzo Da Ponte's libretto for Cos ︡fan Tutte is on female infidelity, two partner-swapping couples, and a wager. Its enigmatic ambiguity and lightness of touch, its razor's edge balance between irony and empathy, detachment and involvement, and on-stage reality and illusion is structured with perfect Classical symmetry. More than any other opera it explores the depths and darker impulses of the experience of love
Interpreten unter anderem: Valentina Nafornita (Fiordiligi). Vasilisa Berzhanskaya (Dorabella). Mattia Oliveri (Guglielmo). Matthew Swenson (Ferrando). Benedetta Torre (Despina). Thomas Hampson (Don Alfonso). Orchestra e Coro del Maggio musicale Fiorentino. Zubin Mehta (Dirigent)
Aufnahme: Florenz, Teatro del Maggio Musicale Fiorentino, 28. März 2021
Keywords: Operas; Filmed performances; Opera films; Films d'opéra; Spectacles filmés; Film; Blu-Ray-Disc